Pengamalan Bentuk-Bentuk Komunikasi Dakwah Pendakwah Orang Asli - Aini, Z.; Don, A.G.; Mokhtar, A.I.; Nor Sad, N.H.D. (Universiti Sains Islam Malaysia, 2024)
This article is a fieldwork study done toward the muslim preachers who preach Islamic teaching to the Orang Asli community in Selangor. It involves the approach and communication skills that are used in conveying the message to the target group of da`wah. Therefore, this study aims to identify the types of dakwah communication used by the preachers in order to convey the dakwah messages to the target group namely the aboriginal (Orang Asli) community. This qualitative study utilizes the case study design. Eight preachers from Penggerak Masyarakat Orang Asli (PMOA) and Panel Dakwah Muallaf (PDM) in Selangor and a research informant are chosen for interviews. The data are organised and coded based on the themes and categories obtained from the complete transcriptions. Then, the data are analyzed descriptively. The findings show that there are three initial processes used by the preachers in developing the types of dakwah communication. It involves the initiatiation stage, planning as well as the preparation to begin a conversation on a certain topic when communicating with the Orang Asli. In order to ensure effective communication, the preachers is were not only applying verbal communication, but also non-verbal communication in order to open the channel of communication for dakwah. All the three stages influence the efficacy of the dakwah messages presented and give positive impacts towards Orang Asli community.